The partner link worker: A vital but undervalued service for women who have been subjected to or at risk of domestic abuse - Woolford, Rebecca Jayne (Probation journal, 2023)
This study aims to explore the partner link worker (PLW) role in supporting women who have been subjected to or at risk of domestic abuse. Prior research in a probation setting tends to focus solely on the person on probation, failing to examine the experiences of people subjected to crime and support services on offer. The PLW role provides an essential service that has been undervalued and overlooked. The study begins to provide some evidence to counter the broader political rhetoric that people subjected to crime are central to probation practice within the criminal justice system. It draws on the findings from thirteen semi-structured interviews conducted across five Community Rehabilitation Companies (CRCs). The findings suggest that PLWs demonstrate a professional commitment to protecting and safeguarding vulnerable women and addressing domestic abuse. However, PLWs face many challenges and obvious gaps in provisions to provide a fully inclusive and accessible service to meet the individual needs of women and their children. The recently reunified probation service offers an optimum opportunity to review, resource and regenerate the PLW service to protect and safeguard people who have been subjected to or at risk of domestic abuse.